Preparation method of transition metal doped anti-perovskite nitride catalyst
Mo doping modified CuNNi catalyst increases the contact area between the catalyst and the electrolyte, solving the problems of stability and reaction efficiency of seawater electrolytic catalysts under high current density, and achieving long-term stable operation and excellent electrocatalytic performance in alkaline seawater.
Patent Information
- Application Number
- CN202510353490.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-06-20
AI Technical Summary
Seawater electrolytic catalysts are prone to poisoning, corrosion and morphological collapse under high current density, resulting in reduced reaction efficiency and poor stability.
The preparation method of transition metal doped antiperovskite nitride catalyst is adopted to modify CuNNi catalyst by Mo doping, and the contact area between the catalyst and the electrolyte is increased and the catalytic performance is improved.
The modified CuNNi2.25Mo0.75 catalyst exhibits excellent electrocatalytic properties in HER and OER, and has stable operation in alkaline seawater for more than 1000 hours, exceeding the performance of commercial catalysts.
Smart Images

Figure CN120172361A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and particularly to a preparation method of a transition metal-doped anti-perovskite nitride catalyst. Background Art
[0002] With the increasing global demand for energy, the problem of energy shortage has become increasingly prominent, making the task of developing efficient renewable energy more urgent. As a renewable energy source, hydrogen energy is considered one of the most promising energy sources to replace fossil fuels due to its high energy density, abundant reserves, and pollution-free combustion. Currently, most hydrogen production relies on steam methane reforming, and the products obtained by this method will contain some impurity gases such as CH4 and CO, which to some extent limits the application of the products. Hydrogen production by electrolyzing water, whose products are only H2 and O2 without generating impurity gases, has gradually come into the view of scientific researchers, and previous excellent scientific research has provided a lot of support for water electrolysis, showing great application potential of water electrolysis. Due to the abundant reserves of seawater on Earth (about 96.5%), a lot of attention has been placed on seawater electrolysis. Different from pure water, there are a large number of Cl and metal salts in seawater. In the water electrolysis reaction, Cl will adsorb on the active sites of the catalyst, resulting in catalyst poisoning and corrosion of the catalyst, which seriously affects the stability of the catalyst. And metal salts such as Ca 2+ , Mg 2+ and other substances will react with the catalyst surface to form a passivation layer, which causes a decrease in electrolysis efficiency. Moreover, for seawater electrolysis to achieve industrial applications, it is also required that the catalyst remains stable under high currents. At high current densities, the generation of H2 and O2 gases is extremely rapid, which leads to a large amount of gas remaining on the catalyst surface, to some extent affecting the contact between the catalyst and the electrolyte and reducing the reaction rate of the catalyst. Moreover, the accumulation of gas on the surface will also affect the surface structure of the catalyst, causing the collapse of the catalyst morphology and reducing the active area and active sites of the catalyst. To solve the above problems, a series of metal catalysts have been developed, such as metal phosphides, metal nitrides, metal sulfides, and metal hydroxides. Among them, metal nitrides show great application potential due to their excellent stability and catalytic performance.
[0003] As a special metal nitride, inverse perovskite nitride has attracted much attention in the field of electrocatalysis due to its flexible dual sites and excellent electrical conductivity. The general structural formula of inverse perovskite nitride is ANM3, and its crystal structure belongs to the Pm-3m space group. In the cubic unit cell, A is located at the vertex of the cube, B is located at the center of the octahedron, and M is located at the face center of the cube. Moreover, both A and M sites are transition metal elements, indicating the flexibility of its structure. However, its unique electronic configuration affects the adsorption of reaction intermediates, thus reducing the electrocatalytic performance. In previous studies, the Cu-Ni interaction can optimize the Gibbs free energy of the reaction intermediate state. Therefore, we choose CuNNi3 as the research object. However, CuNNi3 still has poor reaction kinetics. Therefore, an electronic structure modulation strategy is selected to design the catalyst to improve its reaction kinetics and make it exhibit excellent electrocatalytic performance.
[0004] For this reason, this paper proposes a preparation method of a transition metal-doped inverse perovskite nitride catalyst. Summary of the Invention
[0005] The present invention designs a preparation method of a transition metal-doped inverse perovskite nitride catalyst, which increases the contact area between the catalyst and the electrolyte and greatly improves the catalytic performance of the catalyst.
[0006] To achieve the above technical effects, the present invention is realized through the following technical solutions: A preparation method of a transition metal-doped inverse perovskite nitride catalyst, characterized by comprising the following steps:
[0007] S1. Material preparation: Weigh Cu(NO3)2·6H2O, Ni(NO3)2·6H2O, (NH4)6Mo7O 24 ·4H2O and urea in a molar ratio of Cu(NO3)2·6H2O:Ni(NO3)2·6H2O:(NH4)6Mo7O 24 ·4H2O:urea = 1000:2000 - 3000:36 - 144:14.
[0008] S2. Add 60 mL of deionized water to a 100 mL beaker, and then add the weighed Cu(NO3)2·6H2O, Ni(NO3)2·6H2O, (NH4)6Mo7O 24 ·4H2O and urea to the deionized water, and stir ultrasonically until evenly dissolved; obtain the prepared solution.
[0009] S3. Take a 4×4 cm nickel foam, wash it with hydrochloric acid for 10 - 20 minutes to remove the surface oxide, and then transfer it to alcohol and deionized water in turn for washing for 10 - 20 minutes and then dry it; obtain the treated nickel foam.
[0010] S4. Transfer the treated nickel foam and the prepared solution together into a 100 mL autoclave. After tightening the autoclave, transfer it to a constant temperature drying oven at a temperature of 110 - 130 °C and dry for 9 - 11 h. After the drying oven cools down to room temperature, take out the autoclave, take out the nickel foam with grown metal oxide / hydroxide, and clean it with deionized water and alcohol to obtain the precursor.
[0011] S5. Place the obtained precursor in a porcelain boat and gently place it in a tube furnace with a heating temperature of 410 - 430 °C for heating for 1.5 - 2.5 h. After the reaction ends and cools down to room temperature, the transition metal doped anti - perovskite nitride catalyst can be obtained.
[0012] Further, in S3, the concentration of the hydrochloric acid is 1 mol / L.
[0013] Further, in S5, the heating rate of the tube furnace is 2 °C / min.
[0014] Further, in S5, the tube furnace is in an NH3 atmosphere during both the heating and constant temperature processes.
[0015] Further, the flow rate of the NH3 is 160 sccm.
[0016] The beneficial effects of the present invention are as follows:
[0017] Through the Mo - doped modified CuNNi 2.25 Mo 0.75 catalyst of the present invention, the morphology of the modified CuNNi 2.25 Mo 0.75 changes, which increases the contact area between the catalyst and the electrolyte and greatly improves the catalytic performance of the catalyst. And the CuNNi 2.25 Mo 0.75 catalyst only requires 30 mV and 292 mV respectively to reach a current density of 10 mA cm -2 in HER and OER; when the catalyst CuNNi 2.25 Mo 0.75 is used as both the cathode and anode of water electrolysis at the same time, the catalyst only requires 1.94 V to reach 500 mA cm -2 , exceeding the commercial catalyst (Pt / C||RuO2), and can stably work in alkaline seawater for more than 1000 h; in - situ Raman shows that the introduction of Mo promotes the formation of the OER active phase NiOOH. Density functional theory (DFT) shows that the introduction of Mo raises the d - band center of Ni, making it closer to the Fermi level, and optimizes the binding of the active site and the oxygen intermediate (UPS also proves this point); compared with the unmodified CuNNi3, CuNNi 2.25 Mo0.75 The Gibbs free energies of different intermediate states in HER and OER are both improved, indicating that the introduction of Mo significantly enhances the electrocatalytic performance of CuNNi 2.25 Mo 0.75 . BRIEF DESCRIPTION OF THE DRAWINGS
[0018] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.
[0019] Figure 1 are the XRD schematic diagrams of CuNNi3 and CuNNi 2.25 Mo 0.75 prepared in the present invention;
[0020] Figure 2 are the SEM schematic diagrams of CuNNi3, CuNNi 2.75 Mo 0.25 , CuNNi 2.5 Mo 0.5 , CuNNi 2.25 Mo 0.75 , CuNNi2Mo1 prepared in the present invention;
[0021] Figure 3 is the HRTEM schematic diagram of CuNNi 2.25 Mo 0.75 prepared in the present invention;
[0022] Figure 4 are the LSV polarization curve schematic diagrams of HER of CuNNi3, CuNNi 2.75 Mo 0.25 , CuNNi 2.5 Mo 0.5 , CuNNi 2.25 Mo 0.75 , CuNNi2Mo1 prepared in the present invention;
[0023] Figure 5 are the LSV polarization curve schematic diagrams of OER of CuNNi3, CuNNi 2.75 Mo 0.25 , CuNNi 2.5 Mo 0.5 , CuNNi 2.25 Mo 0.75 , CuNNi2Mo1 prepared in the present invention;
[0024] Figure 6CuNNi3 and CuNNi prepared according to the present invention 2.75 Mo 0.25 ,CuNNi 2.5 Mo 0.5 ,CuNNi 2.25 Mo 0.75 , Tafel diagram of CuNNi2Mo1 HER
[0025] Figure 7 CuNNi3 and CuNNi prepared according to the present invention 2.75 Mo 0.25 ,CuNNi 2.5 Mo 0.5 ,CuNNi 2.25 Mo 0.75 , Tafel diagram of CuNNi2Mo1 OER
[0026] Figure 8 CuNNi3 and CuNNi prepared according to the present invention 2.75 Mo 0.25 ,CuNNi 2.5 Mo 0.5 ,CuNNi 2.25 Mo 0.75 , Electrochemical capacitance diagram of CuNNi2Mo1 HER
[0027] Figure 9 CuNNi3 and CuNNi prepared according to the present invention 2.75 Mo 0.25 ,CuNNi 2.5 Mo 0.5 ,CuNNi 2.25 Mo 0.75 , Electrochemical capacitance diagram of CuNNi2Mo1 OER
[0028] Figure 10 CuNNi3 and CuNNi prepared according to the present invention 2.75 Mo 0.25 ,CuNNi 2.5 Mo 0.5 ,CuNNi 2.25 Mo 0.75 , Stability diagram of CuNNi2Mo1 HER
[0029] Figure 11 CuNNi3 and CuNNi prepared according to the present invention 2.75 Mo 0.25 ,CuNNi 2.5 Mo 0.5 ,CuNNi 2.25 Mo 0.75,Schematic diagram of the OER stability of CuNNi2Mo1. Specific implementation manners
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0031] Example 1
[0032] 1) Preparation of CuNNi3 precursor
[0033] The ordinary hydrothermal method was adopted to prepare the catalyst CuNNi3 precursor. First, a 100 mL beaker was prepared, and 60 mL of deionized water was added thereto. 1 mmol of Cu(NO3)2·6H2O, 3 mmol of Ni(NO3)2·6H2O and 14 mmol of urea were weighed and added to the deionized water, and ultrasonic stirring was carried out until uniformly dissolved. Subsequently, a 4×4 cm nickel foam was taken, washed with 1 mol / L hydrochloric acid for 15 minutes to remove the surface oxide, and then transferred to alcohol and deionized water for washing for 15 minutes respectively and then dried. The treated nickel foam and the prepared solution were transferred to a 100 mL reaction kettle together. After tightening the reaction kettle, it was transferred to an oven, and the constant temperature was 120 °C and the constant temperature time was 10 hours. After the oven cooled to room temperature, the reaction kettle was taken out, and the nickel foam with grown metal oxide / hydroxide was taken out and washed clean with deionized water and alcohol to obtain the precursor.
[0034] 2) Preparation of CuNNi3
[0035] The precursor obtained in 1) was placed in a porcelain boat, smoothly placed in a tube furnace, the heating temperature was 420 °C, the heating time was 2 hours, and the heating rate was 2 °C / min. The whole heating and constant temperature process was carried out in an NH3 atmosphere in the tube furnace. The NH3 flow rate was 160 sccm. After the reaction ended and cooled to room temperature, CuNNi3 was obtained.
[0036] Example 2
[0037] 1) CuNNi 2.75 Mo 0.25 Preparation of precursor
[0038] The ordinary hydrothermal method was adopted to prepare the catalyst CuNNi 2.75 Mo 0.25Preparation of the precursor. First, prepare a 100 mL beaker, add 60 mL of deionized water to it, weigh 1 mmol of Cu(NO3)2·6H2O, 2.75 mmol of Ni(NO3)2·6H2O, 0.036 mmol of (NH4)6Mo7O 24 ·4H2O and 14 mmol of urea, and add them to the deionized water. Stir ultrasonically until they are uniformly dissolved. Subsequently, take a 4×4 cm nickel foam, wash it with 1 mol / L hydrochloric acid for 15 minutes to remove the surface oxide, and then transfer it to alcohol and deionized water for cleaning for 15 minutes respectively, and then dry it. Transfer the treated nickel foam and the prepared solution together to a 100 mL autoclave. Tighten the autoclave and transfer it to an oven. Keep the temperature constant at 120 °C for 10 hours. After the oven cools down to room temperature, take out the autoclave, take out the nickel foam with grown metal oxides / hydroxides, and wash it clean with deionized water and alcohol to obtain the precursor.
[0039] 2) Preparation of CuNNi 2.75 Mo 0.25
[0040] Put the precursor obtained in 1) in a porcelain boat, gently place it in a tube furnace, heat it at a temperature of 420 °C for 2 hours, and the heating rate is 2 °C / min. The atmosphere in the tube furnace is NH3 during the whole heating and constant temperature process. The flow rate of NH3 is 160 sccm. After the reaction ends and cools down to room temperature, CuNNi 2.75 Mo 0.25 is obtained.
[0041] Example 3
[0042] 1) Preparation of the CuNNi 2.5 Mo 0.5 precursor
[0043] Adopt the ordinary hydrothermal method to prepare the catalyst CuNNi 2.5 Mo 0.5 precursor. First, prepare a 100 mL beaker, add 60 mL of deionized water to it, weigh 1 mmol of Cu(NO3)2·6H2O, 2.5 mmol of Ni(NO3)2·6H2O, 0.072 mmol of (NH4)6Mo7O 24 4H2O and 14 mmol of urea were added to deionized water, and ultrasonic stirring was carried out until uniformly dissolved. Subsequently, a 4×4 cm nickel foam was taken, washed with 1 mol / L hydrochloric acid for 15 minutes to remove surface oxides, and then transferred to alcohol and deionized water for washing for 15 minutes respectively, and then dried. The treated nickel foam and the prepared solution were transferred to a 100 mL reaction kettle together. After tightening the reaction kettle, it was transferred to an oven, with a constant temperature of 120 °C and a constant temperature time of 10 hours. After the oven cooled to room temperature, the reaction kettle was taken out, and the nickel foam with grown metal oxides / hydroxides was taken out and washed clean with deionized water and alcohol to obtain the precursor.
[0044] 2) Preparation of CuNNi 2.5 Mo 0.5 Preparation
[0045] The precursor obtained in 1) was placed in a porcelain boat and smoothly placed into a tube furnace. The heating temperature was 420 °C, the heating time was 2 hours, and the heating rate was 2 °C / min. The entire heating and constant temperature process was carried out in an NH3 atmosphere in the tube furnace. The NH3 flow rate was 160 sccm. After the reaction ended and cooled to room temperature, CuNNi was obtained. 2.5 Mo 0.5 .
[0046] Example 4
[0047] 1) Preparation of CuNNi 2.25 Mo 0.75 Precursor
[0048] The catalyst CuNNi 2.25 Mo 0.75 precursor was prepared by the ordinary hydrothermal method. First, a 100 mL beaker was prepared, and 60 mL of deionized water was added thereto. 1 mmol of Cu(NO3)2·6H2O, 2.25 mmol of Ni(NO3)2·6H2O, and 0.108 mmol of (NH4)6Mo7O 24 *4H2O and 14 mmol of urea were added to deionized water, and ultrasonic stirring was carried out until uniformly dissolved. Subsequently, a 4×4 cm nickel foam was taken, washed with 1 mol / L hydrochloric acid for 15 minutes to remove surface oxides, and then transferred to alcohol and deionized water for washing for 15 minutes respectively, and then dried. The treated nickel foam and the prepared solution were transferred to a 100 mL reaction kettle together. After tightening the reaction kettle, it was transferred to an oven, with a constant temperature of 120 °C and a constant temperature time of 10 hours. After the oven cooled to room temperature, the reaction kettle was taken out, and the nickel foam with grown metal oxides / hydroxides was taken out and washed clean with deionized water and alcohol to obtain the precursor.
[0049] 2) Preparation of CuNNi 2.25 Mo 0.75 Preparation
[0050] Put the precursor obtained in 1) in a porcelain boat, gently place it in a tube furnace, heat at 420 °C for 2 hours, with a heating rate of 2 °C / min. The tube furnace is filled with NH3 atmosphere during the entire heating and constant temperature process. The NH3 flow rate is 160 sccm. After the reaction ends and the temperature drops to room temperature, CuNNi is obtained. 2.25 Mo 0.75 。
[0051] Example 5
[0052] 1) Preparation of CuNNi2Mo1 precursor
[0053] The ordinary hydrothermal method was adopted to prepare the catalyst CuNNi2Mo1 precursor. First, prepare a 100 mL beaker, add 60 mL of deionized water, weigh 1 mmol of Cu(NO3)2·6H2O, 2 mmol of Ni(NO3)2·6H2O, 0.144 mmol of (NH4)6Mo7O 24 ·4H2O and 14 mmol of urea were added to the deionized water, and ultrasonic stirring was carried out until uniformly dissolved. Subsequently, a 4×4 cm nickel foam was taken, washed with 1 mol / L hydrochloric acid for 15 minutes to remove the surface oxide, and then transferred to alcohol and deionized water for washing for 15 minutes respectively and then dried. The treated nickel foam and the prepared solution were transferred to a 100 mL reaction kettle together. After tightening the reaction kettle, it was transferred to a drying oven, with a constant temperature of 120 °C and a constant temperature time of 10 hours. After the drying oven cooled to room temperature, the reaction kettle was taken out, and the nickel foam with grown metal oxides / hydroxides was taken out and washed clean with deionized water and alcohol to obtain the precursor.
[0054] 2) Preparation of CuNNi2Mo1
[0055] Put the precursor obtained in 1) in a porcelain boat, gently place it in a tube furnace, heat at 420 °C for 2 hours, with a heating rate of 2 °C / min. The tube furnace is filled with NH3 atmosphere during the entire heating and constant temperature process. The NH3 flow rate is 160 sccm. After the reaction ends and the temperature drops to room temperature, CuNNi2Mo1 is obtained.
[0056] Example 6
[0057] Figure 1 For X-ray Diffraction (XRD) test, three characteristic peaks at 41.8°, 48.6° and 71.2° can be observed in the test results, which correspond to the (111), (200) and (220) crystal planes of CuNNi3 (ICSD No. 239298). In addition, there are no other characteristic peaks, which indicates that the introduction of Mo has successfully replaced the Ni sites and no other peaks are generated;Figure 2 It shows that the morphology will change to varying degrees after doping with different ratios of Mo, and the surface gradually changes from a planar 2D structure to a spherical structure; Figure 3 As shown in the HRTEM image, the lattice fringes of 0.216 nm and 0.187 nm are attributed to the (111) and (200) crystal planes of CuNNi3. This also indicates that this treatment method will not affect the initial structure of the catalyst; Figure 4 and Figure 5 It shows that CuNNi 2.25 Mo 0.75 has the lowest HER and OER overpotentials at a current density of 10 mA cm -2 , which are 30 mV and 292 mV respectively; Figure 6 and Figure 7 The Tafel plots of 2.25 Mo 0.75 show that CuNNi Figure 8 and Figure 9 The electrochemical capacitance plots of 2.25 Mo 0.75 show that CuNNi Figure 10 and Figure 11 The stability plots of HER and OER measured at different current densities show that the catalyst has relatively good stability.
[0058] Example 7
[0059] Electrocatalytic performance test:
[0060] All electrochemical measurements were carried out on a CHI 760e (CH Instruments, Inc., Shanghai, China). The oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) were carried out in a three-electrode system, and the overall water splitting test was carried out in a two-electrode system. A graphite rod was used as the counter electrode, and a Hg / HgO electrode (SCE) was used as the reference electrode. The prepared catalyst was directly used as the working electrode.
[0061] Unless otherwise specified, the linear sweep voltammetry (LSV) polarization curve was obtained at a slow scan rate of 5 mV s -1 and 95% iR compensation. The electrolyte used for the test was 1 mol / L KOH solution (pH = 14). Electrochemical impedance spectroscopy (EIS) analysis was carried out in the frequency range of 0.01 to 10000. In 1 M KOH electrolyte, the open circuit potential was 100000 Hz. All the potentials in this work were calibrated to the reversible hydrogen electrode (RHE) according to the following equation: E RHE = E SCE + 0.096 + 0.0591 × pH. The entire water splitting system used CuNNi2.25 Mo 0.75 It is carried out as both the anode and the cathode in a two-electrode configuration. The electrochemically active surface area (ECSA) is estimated by the double-layer capacitance, which is calculated from the cyclic voltammogram (CV) collected between 10 and 100 mV s -1 in the non-Faradaic potential region in 1 M KOH.
Claims
1. A method for preparing a transition metal-doped antiperovskite nitride catalyst, characterized in that: The following steps are involved: S1. Material preparation: The molar ratio is Cu(NO3)2*6H2O:Ni(NO3)2*6H2O:(NH4)6Mo7O 24 *4H2O:urea=1000:2000~3000:36~144:14000 Weigh Cu(NO3)2*6H2O, Ni(NO3)2*6H2O, (NH4)6Mo7O 24 *4H2O and urea; S2. Add 60 mL of deionized water to a 100 mL beaker, and then weigh Cu(NO3)2*6H2O, Ni(NO3)2*6H2O, (NH4)6Mo7O 24 *4H2O and urea are added to deionized water and ultrasonically stirred until uniformly dissolved; the prepared solution is obtained S3, take 4*4cm nickel foam, wash it with hydrochloric acid for 10-20 minutes to remove the surface oxide, then wash it in alcohol and deionized water for 10-20 minutes and dry it; Obtaining treated nickel foam; S4, transfer the treated nickel foam and the prepared solution to a 100 mL reactor, tighten the reactor and transfer it to a constant temperature drying oven at a temperature of 110-130°C, and dry it for 9-11 hours; after the drying oven cools down to room temperature, take out the reactor, take out the nickel foam with grown metal oxide / hydroxide, and clean it with deionized water and alcohol to obtain a precursor; S5. Place the obtained precursor in a porcelain boat, and place it steadily in a tubular furnace at a heating temperature of 410-430°C for heating for 1.5-2.5 hours. After the reaction is completed and the temperature is cooled to room temperature, a transition metal-doped antiperovskite nitride catalyst can be obtained.
2. The method for preparing a transition metal-doped antiperovskite nitride catalyst according to claim 1, characterized in that: In S3, the concentration of the hydrochloric acid is 1 mol / L.
3. The method for preparing a transition metal-doped antiperovskite nitride catalyst according to claim 1, characterized in that: In S5, the heating rate of the tubular furnace is 2°C / min.
4. The method for preparing a transition metal-doped antiperovskite nitride catalyst according to claim 1, characterized in that: In S5, the tubular furnace is in an NH3 atmosphere during the heating and constant temperature processes.
5. The method for preparing a transition metal-doped antiperovskite nitride catalyst according to claim 4, characterized in that: The flow rate of NH3 is 160 sccm.